Role Playing Learning Models in Improving Students Speaking Ability in MIS Madinatussalam School - Andini Zahara Simanjuntak; Zahroddar; Kholila Harahap; Nur Rahma Bone; Sastri Dalila Siregar (Sufiya Research Institute, 2023)
The purpose of this study was to improve students' speaking skills in the Indonesian subject by applying the Role Playing learning model to fourth graders of Mis Madinatussalam. This type of research is descriptive qualitative research, namely research that utilizes qualitative data and is described descriptively by using two cycles. Each cycle consists of the stages of planning, implementing actions, observing, and reflecting. The subjects in this study were 28 students of class IV Mis Madinatussalam. The object of this research is students' speaking skills. Data collection in this study was carried out using the observation method and the data were analyzed using descriptive analysis techniques. The results showed that in cycle I, the average score of speaking skills obtained was 76.41 and the average percentage obtained was 75.68%, which is in the low category. Then in cycle II, the average speaking skill score obtained was 82 and the average percentage obtained was 90.64%, which is in the high category. The percentage increase from cycle I to cycle II was 14.21%. This shows that there has been an increase in the percentage of students' speaking skills IV Mis madinatussalam. Based on the results of this study, it can be concluded that the application of the Role Playing learning model can improve students' speaking skills in Indonesian class IV Mis Madinatusslam.